Advances in accounting behavioral research. Vol. 17 - Schmitt, Donna Bobek (Advances in accounting behavioral research,, 2014)
Advances in accounting behavioral research publishes high-quality research encompassing all areas of accounting including financial, auditing, taxation, managerial and information systems, addressing a broad range of issues that affect the users, preparers and assurers of accounting information. Further, this research incorporates theory from, and contributes knowledge and understanding to, applied psychology, sociology, management science, and behavioral economics. Volume 17 of Advances in accounting behavioral research exemplifies this focus by including papers investigating group versus individual decision making, decision making under rules versus principal based standards, and white collar crime, among others.